The use of complementary and alternative medicine among Malaysian chronic kidney disease patients - Muhammad Yusuf AS,; Abdul Halim Abdul Gafor,; Shamsul Azhar Shah, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Many of our chronic kidney disease (CKD) patients venture into complementary and alternative medicine (CAM) to seek a cure for the disease beyond conventional management. The objective of this study was to determine the prevalence and pattern of CAM usage; and its association with the progression of CKD in our population. This was a cross-sectional survey recruited CKD patients from Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Data was collected via interview using questionnaires which explore the demographics, type and pattern of CAM use. Patients’ comorbidities and serum creatinine were extracted from the medical notes to assess the association between progression of CKD and usage of CAM. Chi-square, Independent Samples t-test, Mann-Whitney U test and logistic regression were used to evaluate for an association. Three hundred and seventy two eligible patients were recruited. The prevalence of CAM use was 29% in the past year. Younger age, higher education and higher income level were associated with significantly more usage of CAM. Natural products were the commonest type of CAM used (86.1%). The belief in the effectiveness of CAM was the main reason for its uptake and about 57.8% revealed their practice to their physician. We found that the use of CAM in Malaysian CKD patients did not influence the progression of the disease.